2021
DOI: 10.3390/life11101066
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Combined with Chemoembolization for Locally Advanced Hepatocellular Carcinoma with Macroscopic Vascular Invasion: A Propensity Score Analysis

Abstract: The purpose of this study was to compare the efficacy and safety of transarterial chemoembolization (TACE) plus sorafenib with those of TACE alone in patients with locally advanced hepatocellular carcinoma (HCC). Treatment-naïve patients with preserved hepatic reserve (Child–Pugh score ≤ 7) who received TACE plus sorafenib (n = 91) or TACE alone (n = 109) for locally advanced HCC with macrovascular invasion were retrospectively evaluated. Propensity score matching (PSM) was used to correct selection bias, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Moreover, in this study, propensity score matching (PSM) was used to minimize the influence of selection bias and potential confounders, thus reducing the experimental error, which was worthy of recommendation. 19 Park et al 20 found that sorafenib combined with c-TACE significantly improved TTP, PFS, and tumor response rates in advanced HCC patients compared with sorafenib alone, although it did not improve OS. Patients in the trial who received ⩾2 c-TACE treatments had significantly longer survival than those who received sorafenib alone.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this study, propensity score matching (PSM) was used to minimize the influence of selection bias and potential confounders, thus reducing the experimental error, which was worthy of recommendation. 19 Park et al 20 found that sorafenib combined with c-TACE significantly improved TTP, PFS, and tumor response rates in advanced HCC patients compared with sorafenib alone, although it did not improve OS. Patients in the trial who received ⩾2 c-TACE treatments had significantly longer survival than those who received sorafenib alone.…”
Section: Discussionmentioning
confidence: 99%
“…[15] One important question regarding the treatment of patients with liver-restricted tumors who are eligible for non-surgical local treatment is whether adding systemic treatment to locoregional treatment improves outcomes. Several retrospective studies [16][17][18][19][20] and ongoing prospective studies have investigated the combined use of TACE and the tyrosine kinase inhibitor sorafenib in patients with advanced disease. [21,22] The results of the first major phase III randomized trial of sorafenib with TARE and SORAMIC have been reported at the 2018 International Liver Congress.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled trial from South Korea ( 10 ), chemoembolization plus external beam radiotherapy showed better median OS than sorafenib treatment (14 vs. 11 months, P=0.04) in HCC patients with MVI. In addition, chemoembolization combined with systemic therapy (sorafenib or lenvatinib) showed promising outcomes in HCC patients with MVI ( 11 , 12 ). Above all, a sizable study regarding clinical outcomes of atezolizumab plus bevacizumab systemic treatment for HCC with MVI is eagerly waited.…”
mentioning
confidence: 99%